Tecnología y percepción social evaluar la competencia tecnológica - Jorge A. González (Estudios sobre las Culturas Contemporáneas)
As a part of a set of different research tools created into a major project called "Relationships between Technology and Culture in Mexico", the author presents and briefly discusses an instrument through which the social agent self perception of technological competence can be estimated. The instrument has been designed to evaluate the scores of a single agent submitted to a continuum of 42 different technological tools. Grounded fieldwork shows crucial issues regarding education policy.